The welfare state as a public good not excludable - Accinelli, Elvio; Salas, Osvaldo (Estudios Económicos de El Colegio de México, 2019)
In this work, we analyze the possible evolution of an economy in which,up to a certain point, the State acted as a monopolist in the provision of a set of public services and, faced with a change in the economic situation, poses itself, the question about whether these services should continue to be, as they were until then, provided by the State or, if the service should be handed over to private individuals. Regardless of the answer to this question, it is assumed that they should be provided without exclusions and with the same quality to all citizens regardless of their wealth. This is a basic principle that guides the economies of countries that, like Sweden, are governed by the rules of the welfare state. We introduce a model based on game theory to analyze the evolution of this process and its possible outcomes.